Factors Predicting COVID-19 Vaccination Uptake Among Men Who Have Sex With Men in China: An Observational Prospective Cohort Study - Zhang, Kechun; Chan, Paul Shing-fong; Chen, Siyu; Fang, Yuan; Cao, He; Chen, Hongbiao; Hu, Tian; Chen, Yaqi; Zhou, Xiaofeng; Wang, Zixin (Frontiers in Medicine, 2022)
Background: The coronavirus disease 2019 (COVID-19) pandemic has disproportionately affected sexual minorities including men who have sex with men (MSM). This study investigated factors associated with the uptake of COVID-19 vaccination among MSM in China. Methods: Inclusion criteria were: 1) born biologically male, 2) had oral or anal sex with men in the past year, 3) aged at least 18 years, and 4) lived in Shenzhen, China. Prospective participants were recruited through outreach in gay bars and saunas, online recruitment, and peer referrals. Participants completed a baseline online survey between August and September 2020 and a follow-up online survey between April and May 2021. Logistic regression models were fitted for data analysis. Results: Among 420 participants who completed the baseline survey, 303 completed the follow-up survey. Among participants being followed up, 113 (37%) received at least one dose of COVID-19 vaccination during the study period. After adjusting for significant sociodemographic characteristics, five baseline predisposing factors predicted COVID-19 vaccination uptake during the follow-up period, including asking whether their partners had COVID-19 symptoms (adjusted odds ratio (AOR): 1.17, 95% confidence interval (CI): 1.00-1.38), washing hands before and after sex (AOR: 1.23, 95% CI: 1.03-1.46), sanitizing before and after sex (AOR: 1.17, 95% CI: 1.00-1.37), perceived higher risk of COVID-19 transmission through sexual behaviors (AOR: 1.28, 95% CI: 1.04-1.58), and panic about COVID-19 (AOR: 1.48, 95% CI: 1.16-1.89). Regarding enabling factors, receiving testing for sexually transmitted infections (STI) (AOR: 2.19, 95% CI: 1.25-3.85) and other prevention measures for human immunodeficiency virus (HIV)/STI (AOR: 2.61, 95% CI: 1.56-4.37) six months prior to the baseline survey were associated with higher uptake of COVID-19 vaccination. Conclusions: MSM’s uptake rate of COVID-19 vaccination was comparable to that of the general population in Shenzhen, China. This study offered an overview for us to identify tapping points that can encourage COVID-19 vaccination uptake among Chinese MSM.